Overexpression of associated with altered genome and poor survival in selected types of human cancer - Oanh TN Tran; Serkalem Tadesse; Christopher Chu; Dawit Kidane (Tumor Biology, 2020)
Base excision repair, which is initiated by the DNA N -glycosylase proteins, is the frontline for repairing potentially mutagenic DNA base damage. Several base excision repair genes are deregulated in cancer and affect cellular outcomes to chemotherapy and carcinogenesis. Endonuclease VIII-like 3 (NEIL3) is a DNA glycosylase protein that is involved in oxidative and interstrand crosslink DNA damage repair. Our previous work has showed that NEIL3 is required to maintain replication fork integrity. It is unknown whether NEIL3 overexpression could contribute to cancer phenotypes, and its prognostic value and use as potential drug target remain unexplored. Our analysis of cancer genomics data sets reveals that NEIL3 frequently undergoes overexpression in several cancers. Furthermore, patients who exhibited NEIL3 overexpression with pancreatic adenocarcinoma, lung adenocarcinoma, lower grade glioma, kidney renal clear cell carcinoma, and kidney papillary cell carcinoma had worse overall survival. Importantly, NEIL3 overexpressed tumors accumulate mutation and chromosomal variations. Furthermore, NEIL3 overexpressed tumors exhibit simultaneous overexpression of homologous recombination genes (BRCA1/2) and mismatch repair genes ( MSH2/MSH6 ). However, NEIL3 overexpression is negatively correlated with tumor overexpressing nucleotide excision repair genes ( XPA, XPC, ERCC1 / 2 ). Our results suggest that NEIL3 might be a potential prognosis marker for high-risk patients, and/or an attractive therapeutic target for selected cancers.